Complications Associated with Glucocorticoids Treatment in Critically Ill Patients - Confalonieri, Paola; Reccardini, Nicolò; Kette, Stefano; Salton, Francesco (Seminars in Respiratory and Critical Care Medicine, 2025)
Glucocorticoids (GCs) are essential immunomodulatory agents in the management of critically ill patients with severe systemic inflammation, particularly in conditions such as sepsis, acute respiratory distress syndrome, and severe community-acquired pneumonia. When administered in low-to-intermediate doses for short durations (typically ≤4 weeks, including tapering), GCs have demonstrated substantial benefits in improving patient-centered outcomes, including reduced time on mechanical ventilation, shorter ICU stays, and lower mortality rates. However, the risk-benefit profile of GC therapy in critical illness differs markedly from long-term use in chronic inflammatory diseases and must be carefully evaluated. This study provides an evidence-based synthesis of the most relevant complications associated with the use of GCs in critically ill adults. Hyperglycemia is the most frequent metabolic effect, but it is typically transient and manageable with insulin, and is not associated with worse clinical outcomes. The risk of nosocomial infections has not been shown to increase significantly with appropriate dosing; in fact, immunomodulation by GCs may improve bacterial clearance. Nevertheless, clinicians should remain vigilant for opportunistic infections, particularly invasive fungal infections, in high-risk populations such as those with COVID-19. Musculoskeletal effects, including ICU-acquired weakness, appear to result more from underlying disease and immobilization than from GCs themselves, especially at moderate doses. Neuropsychiatric and gastrointestinal complications are dose-dependent and generally reversible. The transient suppression of the hypothalamic–pituitary–adrenal axis underscores the importance of gradual tapering to prevent inflammatory rebound and adrenal insufficiency. Overall, contemporary data support the safety of GCs when used with precision, directed by patient severity and response to treatment, with careful tapering and monitoring. The incorporation of integrative strategies, such as micronutrient and probiotic supplementation, may enhance GC receptor function and reduce required doses, further improving outcomes. Recognizing and managing potential complications enables clinicians to harness the therapeutic potential of GCs in critical illness fully.
Keywords: critically ill patients; immunomodulatory agents; systemic inflammation; glucocorticoid therapy